Issues and Challenges of Saudi Female Labor Force and the Role of Vision 2030: A Working Paper - Sana Naseem; Kamini Dhruva (International Journal of Economics and Financial Issues, 2017)
Female labor force participation plays a key role in economic development. The Kingdom of Saudi Arabia (KSA), as a developing economy, relies mainly on men rather than women to achieve its development objectives. Over a period of fifty years, Saudi female labor force participation is extremely low. This working research paper seeks to identify the challenges and issues of the female labor force in KSA.  The study has employed regression model, in which the dependent variable is Female LFPR and independent variables are unemployment rate (u-rate), urban population, fertility rate & higher education. The results have shown that u-rate, fertility rate and urban population show statistical significance on Female LFPR, except higher education. It has been concluded that despite the challenges faced by the female labor force in Saudi Arabia, Vision 2030 paves a new path to empower women to contribute to the economic growth of the Kingdom.